The Effect of pH Values on Suspended Microorganisms Growth in Tofu Wastewater Treatment - Restu Hikmah Ayu Murti; Rizka Novembrianto; Firra Rosariawari; Munawar Ali (Future Science)
Tofu industry produces the waste that contains a lot of organic substances. The waste is discharged into the environment without any treatment process, it will cause the environmental pollution. In Indonesia, tofu industries (the small-scale industry) mostly do not treat their waste due to the problem of the high cost treatment process. The purpose of this research is to know the effective and economically reasonable that can be used by tofu producers to process tofu waste, especially liquid waste so not damage the environment. Water treatment process using bacterial from waste water as medium seems promising to develop since it does need any bacteria starter or other media like glucose. The other reason is wastewater from food processing is more suitable for microorganism cultivation because its effluent contains significant beneficial nutrient and less of toxic compounds and harmful substances that interface with the growth of microorganism in same condition (pH and Temperature) in Acclimatization process can reach 83.2% after 7 days of treatment. After the detention time (18 hours) the results of COD number also greatly decrease with 2.5 hours recirculation at 12 L/min air and pH 3.7 and 4.5 it can reach 85% and 86% of removal COD.